1974
DOI: 10.1017/s0008423900048587
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Group Socialization among German Students

Abstract: When compared to research on the family and the school, the study of peer groups within the context of political socialization is a relatively neglected area. Somewhat more concern for peer-group effects has been indicated by non-political social scientists, especially social psychologists. But even though some of their work is suggestive, its application is often marginal for explaining political attitudes. Just as the existing theory on peer-group political socialization is weak, so are the existing data and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…And they also have the same perception if they discussion the event with their families and friends more. The above findings are consistent with the arguments of Maccoby et al (1954): family plays an important role in political socialization; and also supports the thinking of Chandler (1974): peers' suggestions might influence young people's political preferences. Besides, the results also support the findings of van Deth et al Apparently, political socialization starts in the family and continues throughout the life of the individual (Sapiro, 2004;Schwarzer, 2011), peer influence begins during adolescence, and media continuously influences the long-term development of political socialization.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…And they also have the same perception if they discussion the event with their families and friends more. The above findings are consistent with the arguments of Maccoby et al (1954): family plays an important role in political socialization; and also supports the thinking of Chandler (1974): peers' suggestions might influence young people's political preferences. Besides, the results also support the findings of van Deth et al Apparently, political socialization starts in the family and continues throughout the life of the individual (Sapiro, 2004;Schwarzer, 2011), peer influence begins during adolescence, and media continuously influences the long-term development of political socialization.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…On the contrary, they urge that it is important to understand the effectiveness of this agent as a source for political socialization (Langton, 1967;Campbell, 1980). Chandler (1974) suggested that although the family's influence is hardly deniable, there is a fact that could explain why their peer group could wield influence over young people. He explained that while in the household the strongest opinions are usually reserved for the parents, in the peer group everyone seizes equal rights to express thoughts and disagreements.…”
Section: Peersmentioning
confidence: 99%
“…The school environment has further been widely identified as a major source of peer influence on political attitudes (Hess & Torney, 1968;Nie, 1996). Chandler (1974) suggested that although the family's influence is hardly deniable, peer's opinions also hold a strong force on young people's cognition of things around. He explained that while in the household the parents usually reserve the strongest opinions; in the group of peers, expressing thoughts and disagreements is a back-and-forth interaction where everyone could hold a standpoint.…”
Section: Political Socialization In Singapore Schools and The Workplacesmentioning
confidence: 99%